EDUKASI ETIKA KOMUNIKASI PENGGUNAAN EMPAT KATA AJAIB TERHADAP ANAK SANGGAR SUNGAI DELI - Susanti, Sani; Tussolihin, Khodijah; Almarind, Marisa; Syahputri, Nurlailly; Damaiyana, Desi; Ariani, Devi (Jurnal Insani, 2024)
The quality of the young generation is a reflection for the future of the nation. Character education, academic education, creativity education, and communication education must be implemented properly. Ethics is a very important education because it concerns a person's morality in behaving and communicating. The purpose of this research is to foster good morals and ethics and must be trained and taught to every individual from a young age. Communication ethics are also influenced by moral principles in accordance with the social environment. Communication is not just about talking, conveying messages, receiving messages, and processing them. If children are unable to communicate, then children can have difficulty learning, socializing, and even achieving their goals. This research uses a descriptive qualitative approach. The method used was observation related to the venue and discussion interviews with the management of the Deli River Studio. The implementation of the activity was carried out by providing material and playing together This research activity yielded results in the form of material regarding communication ethics education that was well received by the children of the Deli River Studio. Therefore, the hope in the future is that the children of Sanggar Sungai Deli will get a proper education, especially character education, especially in communication.